Editorial - Klausen, Søren Harnow (Res Cogitans, 2018)
This special issue of Res Cogitans presents a selection of the papers presented at the conference Frontiers in the philosophy of literature, which was held at the University of Southern Denmark, Odense from 25-26th September 2015. The conference was funded by the Danish Research Council for Independence Research – Humanities and hosted by the Department for the Study of Culture. It focused three interrelated topics that are both more or less perennial questions in the philosophy of literature and at the same time have attracted renewed attention, and received important modifications, in light of recent developments in literature, philosophy and society at large.